The Influence of African Continentl Free Trade Are on Indonesian Palm Oil Eports to Africa - Alfian, Alfian; Harahap , Ali Musa; Candra, Rudi (Mediasi Journal of International Relations, 2024)
African Continental Free Trade Area provides easy access for commodity markets on the African continent that were previously hampered, easy market access also provides a great opportunity for commodities to experience a decline in availability that was previously not felt. there is an increase in Indonesian palm oil exports to African countries after the agreement of the African Continental Free Trade Area. This research look for how does the African Continental Free Trade Area affect Indonesia's palm oil exports to the African Continent. The method in this research is a qualitative research method. secondary data is used to find answers in this research, trade cooperation and regionalism used to explain the phenomenon, The influence of the African Continental Free Trade Area affects the export activities of Indonesian palm oil which results in an increase in the number of Indonesian palm oil exports to Africa. Good relations between Indonesia and countries on the African continent that have been established for a long time and Indonesia's ability as the largest producer of palm oil products in the world is the right reason for African countries to choose palm oil imports from Indonesia,.